2008
DOI: 10.1590/s0124-00642008000100009
|View full text |Cite
|
Sign up to set email alerts
|

Demora en el Diagnóstico de Tuberculosis Pulmonar en una región de Colombia

Abstract: Average delay time for diagnosing pulmonary tuberculosis was 120 days. This was higher than in other studies which have reported delay as being 42 to 119 days. We recommend expediting the diagnosis of pulmonary tuberculosis so that other people do not become infected and improving health service commitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
15

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 1 publication
0
7
0
15
Order By: Relevance
“…Similar reasons were described in another study: patients "thought symptoms would go away" and "symptoms not considered serious" 13 . It has also been reported that patients awaiting symptoms resolution without specific treatment and can assign them to viral infections 26,27,28,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar reasons were described in another study: patients "thought symptoms would go away" and "symptoms not considered serious" 13 . It has also been reported that patients awaiting symptoms resolution without specific treatment and can assign them to viral infections 26,27,28,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Varios estudios han denominado como "retraso diagnóstico" al tiempo comprendido entre el inicio de síntomas y el diagnóstico de tuberculosis pulmonar, y lo han reportado con un promedio de 1 a 2 meses (7,8). En nuestro país, en un estudio realizado en Bucaramanga se encontró una mediana de 120 días para establecer el diagnóstico de la enfermedad, asociada a factores como el desempleo y la falta de cobertura en salud (8).…”
Section: Discussionunclassified
“…En nuestro país, en un estudio realizado en Bucaramanga se encontró una mediana de 120 días para establecer el diagnóstico de la enfermedad, asociada a factores como el desempleo y la falta de cobertura en salud (8). En otros países han reportado otros factores que contribuyen a un mayor tiempo para establecer el diagnóstico, como son el costo de la atención médica, el desconocimiento de la enfermedad por parte del paciente, los prolongados tiempos de espera en los servicios de salud, y la falta de sospecha y búsqueda de la enfermedad por parte del personal de salud (9-15).…”
Section: Discussionunclassified
“…Although the male gender assumes greater role in the profile of TB morbidity and mortality, men delayed their search for health care services more than women. About this aspect, differences exist in the literature showing that the expression of gender is diverse within each country: the same result was obtained in India (5) ; in Colombia, there was no difference in the time of seeking care between men and women (10) but, in Tanzania (4) , by reasons related to cultural aspects incurred in the absence of autonomy and access to financial resources, women delayed to seek TB diagnosis. Another aspect to be considered referred to the predominance of delay among 18-29 years old patients, which revealed the tendency of these individuals support economically the family and also the influence of the health services opening hours in the pattern of seeking care behavior (7,11) .…”
Section: Discussionmentioning
confidence: 98%